IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI KECAMATAN KINOVARO KABUPATEN SIGI - Hasman, Rasmah (Katalogis, 2015)
This research aims at ascertaining The Implementation of Village Fund Allocation Policy in Kinovaro Sub-district, Sigi Regency. This research uses Edward III theory, namely communication, disposition, bureaucracy structure, and resource. This research uses a qualitative approach. The research setting and informants were determined purposively. The collected data were analyzed in stages based on the information from the sample which obtained from observations, interviews, and documentations. The informants are 5 (five) persons. The techniques of the data collection are observations, interviews, and documentations. The results of this research show that: the implementation of village fund allocation policy in Kinovaro Sub-district, Sigi Regency is not optimal yet. Because from four indicators investigated, three of them did not run well, they are communication (lack of socialization), resource (human resource and facilities and infrastructure are inadequate), disposition (lack of commitment), the only indicator that runs well is bureaucracy structure.